2010
DOI: 10.20885/eksakta.vol11.iss2.art6
|View full text |Cite
|
Sign up to set email alerts
|

Redox Reaction in the Cyclization-Aromatization of (R)-(+)-Citronellal With Fecl3/Acetic Anhydrid

Abstract: The effects of temperature, time of reaction, and the reactants mole ratio on the cyclizationacetylation of (R)-(+)-citronellal with FeCl 3 /acetic anhydride were studied. Isopulegyl acetate (IPA) and neoisopulegyl acetate (NIPA) were obtained as the main products at room temperature (mole ratio of citronellal: acetic anhydride: FeCl 3 = 6:12:1). Both products are relatively fixed after the 30th minute. The average concentration of IPA at 30-180 minutes was 44.71%, while the average concentration of NIPA was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Citronellal is one of monoterpenes in citronella oil. The citronellal content of high quality oil is 28-45% [1]. Citronellal has two optical isomeric with molecular weight of 154.25.…”
Section: Introductionmentioning
confidence: 99%
“…Citronellal is one of monoterpenes in citronella oil. The citronellal content of high quality oil is 28-45% [1]. Citronellal has two optical isomeric with molecular weight of 154.25.…”
Section: Introductionmentioning
confidence: 99%
“…Soil is one of the important land components in providing agricultural products. As a growing medium for plants, soil has the role of storing and supplying the nutrients needed by plants [1]. Fertile soil has the characteristics of a deep profile, loose structure, neutral pH, sufficient nutrient content for plants, and there are no limitations in the soil for plant growth [2].…”
Section: Introductionmentioning
confidence: 99%
“…Soil erodibility studies on each slope are needed, especially in areas that have the potential for soil erosion, such as in the Nawungan, to be able to adapt appropriate soil conservation techniques at the research location. Based on the background explained previously, the objectives of this research were to: (1) analyze the erodibility index at each different slope at the research location and (2) evaluate the effect of soil erodibility on the potential productivity of agricultural land at the research location.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclysation-acetylation of citronellal with FeCl3 Catalyzed showed that in high temperature selectivity to produce IPA was low, and the major product was p-cymene as the side product [10].…”
Section: Introductionmentioning
confidence: 99%